Strategi Produksi Konten untuk Penguatan Branding Akun Instagram @themiracleofcom - Ayu Widiastuti; Isnawijayani Isnawijayani; Dwi Muhammad Taqwa (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
The Independent Project's implementation of the Strategic Content Iteration Program (SCIP) on the Instagram account @themiracleofcom aimed to design a content production strategy to strengthen the branding of the @themiracleofcom Instagram account. The results of the service demonstrated that the implementation of the SCIP program was highly effective in significantly improving account performance. This was demonstrated by the achievement of 2,210 new followers, exceeding the initial target of 442%. This success was driven by an adaptive and data-driven content strategy through the PDCA cycle.